Luminosity measurements for the R scan experiment at BESIII *Supported by National Key Basic Research Program of China (2015CB856700), National Natural Science Foundation of China (NSFC) (10935007, 11121092, 11125525, 11235011, 11322544, 11335008, 11375170, 11275189, 11079030, 11475164, 11475169, 11005109, 10979095, 11275211), Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (11179007, U1232201, U1332201, U1532102). (KJCX2-YW-N29, KJCX2-YW-N45). 100 Talents Program of CAS, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology, German Research Foundation DFG (Collaborative Research Center CRC-1044), Istituto Nazionale di Fisica Nucleare, Italy, Ministry of Development of Turkey (DPT2006K-120470), Russian Foundation for Basic Research (14-07-91152), U. S. Department of Energy (DE-FG02-04ER41291, DE-FG02-05ER41374, DE-FG02-94ER40823, DESC0010118), U.S. National Science Foundation, University of Groningen (RuG) and the Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt, WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (June 2017) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ahmed, S.; Ai 艾, X. C. 小聪; Albayrak, O.; Albrecht, M.; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Bakina, O.; et al.
Abstract: By analyzing the large-angle Bhabha scattering events e + e − → ( γ )e + e − and diphoton events e + e − → ( γ ) γγ for the data sets collected at center-of-mass (c.m.) energies between 2.2324 and 4.5900 GeV (131 energy points in total) with the upgraded Beijing Spectrometer (BESIII) at the Beijing Electron-Positron Collider (BEPCII), the integrated luminosities have been measured at the different c.m. energies, individually. The results are important inputs for the R value and J/ ψ resonance parameter measurements.